Religious Orientations in Pancasila Student Projects: Insights from the Merdeka Curriculum - Suhartono Suhartono; Achmad Basari Eko Wahyudi; Moh. Salimi; Ratna Hidayah; Wahyono Wahyono; Hasan Zainuri; Siti Fatimah; Anesa Surya (AL-ISHLAH: Jurnal Pendidikan, 2025)
The Merdeka Curriculum represents an educational reform aimed at enhancing the quality of learning in Indonesia. A central component of this curriculum is the Project for Strengthening the Profile of Pancasila Students (P5), which seeks to cultivate students’ core values, including religious character. However, the religious dimension of the P5 profile remains underexplored, especially at the elementary level. This study analyzes the implementation of the P5 project in developing students’ religious profiles in elementary schools in Kebumen, focusing on Grades I and IV. Data were collected using focus group discussions, interviews, observations, and documentation. The data were analyzed using the Miles and Huberman model, involving data condensation, data display, and conclusion drawing/verification. Findings reveal that students exhibit strong religious characteristics across five indicators: religious behavior (88.75%), personal behavior (88.50%), social behavior (87.88%), environmental behavior (80.50%), and national behavior (88.00%). These outcomes place the religious attitudes of students in the "excellent" category. Schools employed various strategies to instill religious values aligned with the P5 framework. These included narrative-based instruction, daily habituation practices, and teacher modeling to foster faith, piety toward God, and noble conduct. The implementation of P5 in the religious dimension has been effective in cultivating strong religious attitudes among elementary students. These findings highlight the importance of integrated character-building approaches within the Merdeka Curriculum.